The Pediatric-Specific American Society of Anesthesiologists Physical Status Score: A Multicenter Study. (8th July 2020) - Ferrari, Lynne; Leahy, Izabela; Staffa, Steven J.; Berry, Jay G.
Abstract : BACKGROUND: When applied to the pediatric population, the American Society of Anesthesiologists physical status (ASA-PS) classification has exhibited poor reliability due to its subjective and adult-focused definitions. This study was done to measure interrater agreement of a pediatric-adapted ASA-PS classification and to solicit multicenter perspectives to optimize the pediatric ASA-PS classification. METHODS: A prospective, mixed-methods study of 197 pediatric anesthesiologists from 13 academic pediatric hospitals in the United States, Europe, and Australia surveyed in May and July 2019. Participants assigned ASA-PS scores (I to V) for 15 pediatric cases with a heterogeneous mix of acute and chronic health conditions undergoing a variety of surgical and related procedures. Pediatric-adapted definitions of ASA-PS were provided. The intraclass correlation coefficient (ICC) was used to assess interrater reliability of ASA-PS scores. The ICC was estimated using 2-way mixed-effects modeling, accounting for multiple raters assigning scores for the same set of cases. Qualitative feedback on the pediatric-adapted ASA-PS classification was analyzed with line-by-line coding. RESULTS: The survey response rate was 83.8% (165 of 197). The ICC agreement among participants on ASA-PS scoring across all 15 clinical cases was 0.58 (95% confidence interval [CI], 0.42–0.77). ICC did not vary significantly by years of anesthesiology practice. ICC varied across hospitals (range: 0.34; 95% CI, 0.12–0.63 to 0.79; 95% CI, 0.66–0.91). The highest level of agreement occurred with cases most often scored as ASA-PS I, IV, and V; the lowest agreement occurred with cases most often scored ASA-PS II and III. Clarification of how well a chronic condition was controlled and presence of an acute illness were 2 common themes suggested to optimize the validity of the pediatric-adapted ASA-PS definitions. CONCLUSIONS: The pediatric-adapted ASA-PS classification had moderate interrater reliability among pediatric anesthesiologists. The lower reliability of scoring for ASA-PS II and III cases, in particular, supports the need for further ASA-PS definition refinement for pediatric populations.